The Strain energy density to estimate lifetime of notched components subjected to variable amplitude fatigue loading (Fracture and Structural Integrity, 2018)
In the present paper, the approach based on the strain energy density (SED) averaged over a structural volume is reformulated to estimate the lifetime of notched components subjected to variable amplitude (VA) uniaxial fatigue loading. The accuracy and reliability of the proposed reformulation of the SED approach was checked against a large number of data taken from the literature and generated, under two different load spectra, by testing specimens of carbon steel C40 containing notches of different sharpness. Such a validation exercise allowed us to demonstrate that the extension of the SED approach as proposed in the present paper is capable of accurately estimating fatigue damage in notched components subjected to in-service VA fatigue loading.
Keywords: Strain energy density; Notch; Variable amplitude loading